2018
DOI: 10.1007/s00259-018-4002-7
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline transporter availability on [11C]MRB PET predicts weight loss success in highly obese adults

Abstract: These first longitudinal interventional data on NAT availability in highly obese individuals indicate that the central NA system is modifiable. Our findings suggest that NAT availability before intervention could help predict the amount and success of weight loss in obese individuals and help adjust treatment options individually by allowing prediction of the benefit of a dietary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Consequently, the researchers using 11 C-MRB PET have come to mutual conclusions that the NET availability in the thalamus region of obese adults is decreased when compared to healthy controls (Li et al 2014;Bresch et al 2017). In addition, by measuring the CNS NET availability, it is possible to predict the result of a dietary intervention, and is helpful for adjusting treatment options of highly obese adults (Vettermann et al 2018). BAT plays a role in energy balance and is also regulated by the SNS.…”
Section: C-mrbmentioning
confidence: 99%
“…Consequently, the researchers using 11 C-MRB PET have come to mutual conclusions that the NET availability in the thalamus region of obese adults is decreased when compared to healthy controls (Li et al 2014;Bresch et al 2017). In addition, by measuring the CNS NET availability, it is possible to predict the result of a dietary intervention, and is helpful for adjusting treatment options of highly obese adults (Vettermann et al 2018). BAT plays a role in energy balance and is also regulated by the SNS.…”
Section: C-mrbmentioning
confidence: 99%
“…Despite being the most effective treatment for severe obesity, the understanding of how RYGB affects central neurotransmission, specifically the function of brain monoamines, is still at its beginning. Own previous study using PET and the NAT-selective radiotracer [ 11 C]MRB indicated that NAT availability is a marker of the integrity of the LC-NA system, and that its tone is altered in relation to changes in BMI and BW [16,18,24]. Based on these data, we hypothesized that NAT availability changes 6 months after RYGB surgery in relation to changes in BMI.…”
Section: Discussionmentioning
confidence: 95%
“…A direct relationship, however, between the NA system and changes in body weight (BW) following surgical intervention, i.e., RYGB, has not yet been explored. Based on own previous studies with dietary intervention and a normal weight control group [16,17] and a study by Li et al [18], our general assumption is that NAT availability as a marker of the central noradrenergic tone significantly decreases with reduction in BMI from severe (BMI > 35 kg/ m 2 ) to moderate obesity (BMI 30-35 kg/m 2 ) but increases with reduction from moderate obesity to normal body weight (BMI 18.5-25 kg/m 2 ) describing a U-shaped curve, specifically in the hypothalamus, the insula, and the prefrontal brain area.…”
Section: Introductionmentioning
confidence: 99%
“…The potential implication of changes in the dopaminergic system has been broadly discussed and is reviewed in this special issue [ 2 , 3 ]. The specific role of the other central biogenic amines, i.e., serotonin (5-hydroxytryp-tamine, 5-HT) and noradrenaline (NA), in the pathogenesis of overweight and obesity have, however, been relatively less well explored [ 2 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, carbon-11-labeled methylreboxetine ([ 11 C]MRB) is the clinically most applied radiotracer to visualize and quantify NAT availability in vivo in order to assess whether changes of NA/NAT are associated with excessive weight gain and obesity. Our own previous research on the relationship between NAT availability and BMI indicated a rather reciprocal relationship in the hypothalamus with the lowest BP ND in individuals with modest to high BMI [ 5 , 6 , 7 , 8 ]. Diminished hypothalamic NAT availability in overweight and obesity and an impaired turnover of NA could explain the associated hyperphagia.…”
Section: Introductionmentioning
confidence: 99%